Assessment of Aflatoxin M1 and Heavy Metal Levels in Mothers Breast Milk in Famagusta, Cyprus - Kunter, Imge; Hurer, Nazife; Gulcan, Hayrettin Ozan; Ozturk, Baris; Dogan, Irfan; Sahin, Gonul (Springernature, 2017)
Breast milk contributes towards optimal nutrition for infants. However, studies showed that it can also contain different toxins and heavy metals, which reduce its health benefits. The aim of this study is to determine the level of contaminants such as aflatoxin M1 (AFM1), Pb, Cd, As, and Hg in breast milk samples from Famagusta, Cyprus. Correlations between moldy food consumption, smoking habits of the mothers, and contaminant levels in breast milk were also investigated. Breast milk samples from 50 lactating mothers in rural and urban areas of Famagusta District were analyzed for AFM1 by ELISA. Eighty percent of them were found to be contaminated with AFM1 with the mean measurement of 7.84 +/- 1.72 ng/l. Socio-demographic status, moldy food consumption habits, and smoking status do not have any effect on the AFM1 levels observed in breast milk. Heavy metal levels in breast milk were examined by inductively coupled plasma mass spectrometry, and the mean measurements were1.19 +/- 1.53 ppm for Pb, 0.73 +/- 0.58 ppm for As, 0 +/- 0.20 ppm for Hg, and 0.45 +/- 0.23 ppm for Cd. This study indicates that the levels of these contaminants in breast milk samples obtained in Famagusta District are well within the acceptable levels. However, the presence of AFM1 and heavy metals still may pose risks for infant health.
Keywords: Aflatoxin M1; Breast milk; Heavy metals; Cyprus